2019
DOI: 10.1002/mds.27880
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Discrimination is Altered in Patients With Isolated Asymmetric and Jerky Upper Limb Tremor

Abstract: A BS TRACT: Background: Unilateral or very asymmetric upper limb tremors with a jerky appearance are poorly investigated. Their clinical classification is an unsolved problem because their classification as essential tremor versus dystonic tremor is uncertain. To avoid misclassification as essential tremor or premature classification as dystonic tremor, the term indeterminate tremor was suggested. Objectives: The aim of this study was to characterize this tremor subgroup electrophysiologically and evaluate whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
(179 reference statements)
1
16
0
Order By: Relevance
“…In recent studies, the "canonical" findings of dystonia, such as reduced inhibition and increased plasticity, have been questioned, giving therefore further importance to the network model. For instance, in some studies SICI has been found to be normal (Kojovic et al 2013;Ganos et al 2017;Govert et al 2020) and others have shown a variable response to plasticity protocols in patients with dystonia (Sadnicka et al 2014a). The lack of reproducibility of some results can be attributed to the different reliability of the TMS measures, but the interindividual variability to plasticity-inducing paradigm needs also to be taken into account (Latorre et al 2019).…”
Section: Conclusion: the Network Modelmentioning
confidence: 99%
“…In recent studies, the "canonical" findings of dystonia, such as reduced inhibition and increased plasticity, have been questioned, giving therefore further importance to the network model. For instance, in some studies SICI has been found to be normal (Kojovic et al 2013;Ganos et al 2017;Govert et al 2020) and others have shown a variable response to plasticity protocols in patients with dystonia (Sadnicka et al 2014a). The lack of reproducibility of some results can be attributed to the different reliability of the TMS measures, but the interindividual variability to plasticity-inducing paradigm needs also to be taken into account (Latorre et al 2019).…”
Section: Conclusion: the Network Modelmentioning
confidence: 99%
“…18 For instance, in large samples, although a trend toward a smaller SICI was noticed, this technique could not discriminate dystonic tremor from ET and HS. 21 The same was true FIG. 2.…”
Section: Discussionmentioning
confidence: 62%
“…33 Neurophysiological measures, such as temporal discrimination thresholds, also cannot provide clear distinctions between ET and dystonic tremor, although this may be useful when classifying indeterminate tremors. 34 These findings show that the borders between some clinical tremor syndromes are not fixed, which may indicate a shared pathophysiological basis. 3 Accordingly, it has been argued that 'ET plus' may represent a state condition, such that additional signs emerge during certain stages of ET, 35 or a temporary label, such that patients with ET plus transition to a more definite diagnosis.…”
Section: Movement Disordersmentioning
confidence: 92%